2022
DOI: 10.1111/ijfs.16014
|View full text |Cite
|
Sign up to set email alerts
|

Cassava starch films incorporated with clove essential oil and nanoclay as a strategy to increase the shelf life of strawberries

Abstract: The incorporation of essential oil and nanocomposites can develop bioplastics with antioxidant and antimicrobial effects that extend the shelf life of food. In this study, active cassava starch films were incorporated with clove essential oil (CEO) and montmorillonite (MMT) for application on fresh strawberries. Central composite design was used in the development of cassava starch active films and the mechanical, barrier, antioxidant and antimicrobial properties were evaluated. The effects of active films on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Reinforcing compounds can also be used to improve the characteristics of starch packaging. The starch packing added other compounds like CS (Fonseca‐García et al., 2021), cellulose (Zhang et al., 2023), oils (Gao et al., 2020), proteins (Wu et al., 2023), nanocomposites (Alves‐Silva et al., 2022; Ni et al., 2018; Xu et al., 2023), nanocrystals (Ren et al., 2023), and agro‐industrial waste (Bhat et al., 2013). When added to other compounds, this kind of package is called “composites.” The results of the studies are very promising for the food industry.…”
Section: Starch‐based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcing compounds can also be used to improve the characteristics of starch packaging. The starch packing added other compounds like CS (Fonseca‐García et al., 2021), cellulose (Zhang et al., 2023), oils (Gao et al., 2020), proteins (Wu et al., 2023), nanocomposites (Alves‐Silva et al., 2022; Ni et al., 2018; Xu et al., 2023), nanocrystals (Ren et al., 2023), and agro‐industrial waste (Bhat et al., 2013). When added to other compounds, this kind of package is called “composites.” The results of the studies are very promising for the food industry.…”
Section: Starch‐based Materialsmentioning
confidence: 99%
“…, nanocomposites(Alves- Silva et al, 2022;Ni et al, 2018;Xu et al, 2023), nanocrystals(Ren et al, 2023), and agro-industrial waste(Bhat et al, 2013). When added to other compounds, this kind of package is called "composites."…”
mentioning
confidence: 99%
“…The solubility in water (SW) of films was obtained according to Alves-Silva et al 1,21 The films were cut in 2 cm of diameter and dried in an oven (DeLeo A15E, Porto Alegre, Brazil) for 24 h at 105 C to determine the initial dry weight (W 0 ). The films were submerged in 50 mL of distilled water and homogenized in an orbital shaker (Tecnal TE-420, Piracicaba, Brazil) at 150 rpm for 24 h. Then, the samples were dried again at 105 C for 24 h to determine the final dry weight of the films (W f ).…”
Section: Ts Mpamentioning
confidence: 99%
“…16 Compared to the plums treated with other coatings at 23 ± 2 C, the coating with HPMC containing 2% w/w OEO was shown to be very effective in reducing the respiration rate, ethylene production, total weight loss, and total cell count. 17 Sousa et al reported that cassava starch film containing 0.8% clove essential oil (CEO) exhibited excellent antifungal activity against Colletotrichum gloeosporioides and C. musae. The CEO-loaded film also prolonged the shelf life of banana with good quality and low weight loss.…”
Section: Introductionmentioning
confidence: 99%